Immobilized Microbial Cellulases in Organic-Inorganic Hybrid Materials - Monica Dragomirescu (Scientific Papers Animal Science and Biotechnologies, 2011)
The Aspergillus niger cellulase was immobilized by entrapment in natrium alginate gels and in natrium alginate/silica gel hybrid materials. The silica gels were obtained using two different precursors, tetraethoxysilane (TEOS) and tetramethoxysilane (TMOS), by sol-gel method. Comparing the enzymatic activities of the immobilized products, it was noticed that the CMCase activities obtained in natrium alginate were 1.12-1.17 times higher than those obtained by entrapment in mixed organic – inorganic gels, for similar enzyme loadings. The operational stability was tested in the substrate presence. The cellulase entrapped in the three types of organic-inorganic gel matrices mentioned above retains about 13% of its activity after 4 cycles. After one hour of storage at 37ºC, pH 3.0, the relative activity of the immobilized Aspergillus niger CMCase was more than 98% of initial.